X-Ray Fluorescence Microscopy Demonstrates Preferential Accumulation of a Vanadium-Based Magnetic Resonance Imaging Contrast Agent in Murine Colonic Tumors. Issue 5 (1st May 2015) - Mustafi, Devkumar; Ward, Jesse; Dougherty, Urszula; Bissonnette, Marc; Hart, John; Vogt, Stefan; Karczmar, Gregory S.
Contrast agents that specifically enhance cancers on magnetic resonance imaging (MRI) will allow earlier detection. Vanadium-based chelates (VCs) selectively enhance rodent cancers on MRI, suggesting selective uptake of VCs by cancers. Here we report x-ray fluorescence microscopy (XFM) of VC uptake by murine colon cancer. Colonic tumors in mice treated with azoxymethane/dextran sulfate sodium were identified by MRI. Then a gadolinium-based contrast agent and a VC were injected intravenously; mice were sacrificed and colons sectioned. VC distribution was sampled at 120 minutes after injection to evaluate the long-term accumulation. Gadolinium distribution was sampled at 10 minutes after injection due to its rapid washout. XFM was performed on 72 regions of normal and cancerous colon from five normal mice and four cancer-bearing mice. XFM showed that all gadolinium was extracellular, with similar concentrations in colon cancers and normal colon. In contrast, the average VC concentration was twofold higher in cancers versus normal tissue ( p < .002). Cancers also contained numerous "hot spots" with intracellular VC concentrations sixfold higher than the concentration in normal colon ( p < .0001). No hot spots were detected in normal colon. This is the first direct demonstration that VCs selectively accumulate in cancer cells and thus may improve cancer detection.